Taiwan, Island China - Cooke, David C. (David Coxe), 1917- (New York : Dodd, Mead, 1975)
Discusses the history of Taiwan and its people, culture, and politics today.
Includes index.
Keywords: Taiwan -- Juvenile literature; Taiwan